(untitled) (Sudurpaschim Spectrum, 2023)
This sociological study critically examines the decision-making process of Tharu women in the households of Bhimdatta Municipality, Kanchanpur, Far Western Nepal, with a keen focus on understanding the intricate interplay of sociocultural factors that shape and govern these dynamics, as well as Tharu women’s educational status and decision-making positions in their homes. Research used qualitative and quantitative research methodologies, as well as descriptive and exploratory research, including in-depth interviews and non-participant observations, to investigate the nuanced dimensions of decision-making roles assumed by Tharu women in their familial environments. We included 250 Tharu households. Data from 50 households were gathered to determine a 95% confidence level, 20% population percentage, and 10% margin of error. The study found that Tharu women face significant educational challenges, including limited school access, financial constraints, traditional gender roles, and early marriages, all of which have an impact on their academic advancement and personal development. As a result, the position of decision-making in the Tharu community is far lower than that of men. In the sociological framework, the research study adds to our understanding of gender roles and power dynamics in indigenous societies. This study has important implications for sociological theories about intersectionality, cultural resilience, and adaptation to changing societal norms. Furthermore, the study’s findings have implications for the establishment of more inclusive and culturally responsive policies targeted at promoting gender equity and empowerment in Tharu households and other similar sociocultural settings.